Perbedaan Tingkat Kecemasan antara Pasien Diabetes Melitus Tipe 2 Disertai Komplikasi dengan Tanpa Komplikasi di RSUD Dr. Moewardi - Anggarani, Nia; Nugroho, IGB Indro; Setyawan, Sigit (Nexus Kedokteran Klinik, 2014)
Background: Diabetes mellitus (DM) is referred to as growing epidemic. The prevalence of type 2 diabetes mellitus in Indonesia is 18.6% in urban areas and 9.2% in rural areas. It is estimated that in 2030 the prevalence of DM in Indonesia reached 21.3 million people. Chronic diseases such as diabetes mellitus are associated with the emergence of anxiety disorders. It has been reported that anxiety disorders associated with age, gender, occupation and complications of diabetes mellitus. In addition, an increase in the symptoms of anxiety disorder related to the number and the type of complications suffered by patients with diabetes mellitus. This study aimed to analyze the differences of anxiety level in type 2 diabetes mellitus patients with and without complications in Dr. Moewardi Hospital. Method: 91 type 2 diabetes mellitus patients of Internal Medicine Clinic Dr. Moewardi Hospital participated in a cross-sectional study. 40 patients with complications and 51 patients without complications were recruited with non-probability sampling methods, which was consecutive sampling. Each respondent was given a standard TMAS (Taylor Manifest Anxiety Scale) questionnaire and LMMPI (Lie-scale Minnesota Multiphasic Personality Inventory) questionnaire. The TMAS questionnaire contains 50 questions, which has "yes" or "no" options, and LMMPI questionnaire contains 10 questions, which has "yes" or "no" options. The TMAS questionnaire was employed to estimate the patientsâ symptoms of anxiety. Research data were tested by Chi Square test. Result: The results showed 90% and 70.59% type 2 diabetes mellitus patients with and without complication had anxiety respectively. 8 samples of patients with complications of type 2 diabetes mellitus had severe anxiety, 21 samples had moderate anxiety, and 7 samples had mild anxiety. While in type 2 diabetes mellitus patients without complications, one sample has severe anxiety, 16 samples have moderate anxiety, and 19 samples had mild anxiety. The results of Chi Square test for anxiety in type 2 diabetes mellitus patients showed p < 0.05 (p = 0.024) and for the anxiety level in type 2 diabetes mellitus patients with and without complications showed p < 0.05 (p=0.003). Conclusion: There was difference of anxiety level among type 2 diabetes mellitus patients with and without complications in Dr. Moewardi Hospital. Keywords: type 2 diabetes mellitus with complications, type 2 diabetes mellitus without complications, anxiety levelÂ